(untitled) (Research, Society and Development, 2022)
Objective: To describe the scientific evidence in the literature about the use of flower essence therapy for the treatment of anxiety. Material and methods: This is an integrative review. Articles were searched in two electronic databases: SciELO and BVS. The descriptors "Integrative Medicine;" "Floral Therapy"; "Anxiety" according to the DeCS (Descriptors in Health Science). Articles with full, complete and freely available texts in Portuguese, English or Spanish published from 2017 to July 2022 were selected. The search occurred between June and July 2022. Results: A total of 114 articles were found, and 7 met the inclusion criteria of this research. Three of the papers included in the search dealt with the use of flower essences to control anxiety and stress in women in labor, and two others tested the efficacy of the use of flower essences to control anxiety in children undergoing dental procedures and in overweight and obese people. Final considerations: After analyzing the studies selected for this research, it was possible to identify scientific evidence in the literature proving the efficacy of flower essence therapy on anxiety and stress symptoms in any circumstances in which they are present, whether in labor, in anxiety disorders developed by overweight and obese people, in situations of emotional disorders caused by psychological violence, or in symptoms of generalized anxiety disorder.